Avian Influenza & Human Health (Anwer Khan Modern Medical College Journal, 2014)
The world is now under human pandemic threat by avian influenza viruses. As the human, animal and the environment interact closely from the dawn of the civilization, human health is tremendously influenced by animal health and their health issues. In last few centuries the world has suffered a number of influenza pandemics killing millions of people such as Spanish Flu (1918), Asiatic or Russian Flu (1889-1890), Asian Flu (1957-1958) etc. The exceptional capability of genetic mutation of the influenza viruses offered threats to the whole world time to time. Like all other countries Bangladesh also not away from the heat of the situation. Human cases of avian influenza subtype H1N1, H3, H5N1, and H9N2 have already been reported from Bangladesh. This article reviews the information available on pandemic potential of avian influenza viruses. The article also sheds light on different avian influenza viruses along with some emphasis on clinical and preventive aspects of the avian influenza viral infections, and on avian influenza pandemic preparedness of Bangladesh. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18839 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 35-38